2017
DOI: 10.1667/rr14592.1
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Analysis of Mice Exposed to Gamma Radiation Reveals a Systemic Understanding of Total-Body Exposure

Abstract: Diagnostic markers are needed for accidental or deliberate radiation exposure that could cause acute and chronic radiation toxicity. Biomarkers of temporal, dose-dependent, aging-attenuated and multiple radiation exposures have been previously described by others. However, the physiological origin and biochemical networks that generate these biomarkers and their association at the molecular level have yet to be explored. Hence, the discovery and identification of total-body-irradiation-induced tissue specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 46 publications
1
27
0
Order By: Relevance
“…The utility of 5-oxoproline as a biomarker for NASH is doubtful, as it is often found to be elevated in relation to hepatic oxidative stress. We have recently reported a highly statistically significant upregulation of 5-oxoproline in HepG2 cells treated with the experimental anti-HCV drug [193], in the liver of whole-body γ-irradiated mice [194] and in γ-irradiated HepG2 cells [195].…”
Section: Nafl and Nashmentioning
confidence: 98%
“…The utility of 5-oxoproline as a biomarker for NASH is doubtful, as it is often found to be elevated in relation to hepatic oxidative stress. We have recently reported a highly statistically significant upregulation of 5-oxoproline in HepG2 cells treated with the experimental anti-HCV drug [193], in the liver of whole-body γ-irradiated mice [194] and in γ-irradiated HepG2 cells [195].…”
Section: Nafl and Nashmentioning
confidence: 98%
“…In addition, human serum samples have been analyzed in individuals following radiotherapy 26,27 ; these studies indicated upregulation of biomarkers corresponding to energy metabolism including increased branched chain amino acid synthesis and protein biosynthesis 27 . C57BL/6 mouse biosamples including bone marrow, ileum, muscle, lung, serum, and urine have been analyzed within 12 hours of 6 Gy irradiation and demonstrated differences in DNA methylation pattern, energy expenditure and metabolism of amino acid, glutathione, and bile, respectively 28 . Unlike miRNA profiling, radiation-induced metabolite profiles at various time points relative to radiation exposure warrants further study.…”
mentioning
confidence: 99%
“…Different tissues displayed substantial radiosensitivity. The metabolic signatures were focused on radiosensitive organs in most earlier reports, such as bone marrow, ileum, lung, jejunum and spleen (Golla et al, ; Jang et al, ; Xiao et al, ). Nevertheless, there were few studies on the early metabolic signatures in the brain following irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, novel diagnostic biomarkers and therapeutic targets for clinical applications are also involved in the tissues (Huang et al, ). In recent years, metabolic changes in various tissues including bone marrow, ileum, liver, muscle, lung, jejunum and spleen after ionizing radiation based on liquid chromatography–mass spectrometry (LC–MS) or NMR have been reported (Golla et al, ; Jang et al, ; Xiao, Hu, Liu, & Hu, ). Because of the heterogeneity in chemical properties and wide dynamic range of the metabolites in organism, a single analytical technique is adequate to obtain a global metabolic signature (Wu et al, ).…”
Section: Introductionmentioning
confidence: 99%